Implementasi Budaya (ANTRI) Sekolah dalam Membentuk Karakter Siswa Kelas III di Madrasah Ibtidaiyah Asy-Syifa Kota Bengkulu (Wahana Didaktika : Jurnal Ilmu Kependidikan, 2024)
Cultural implementation is the application of elementary school education based on formal procedures used by elementary schools to uphold educational principles, standards and practices in their educational environment. Schools can also encourage students to think openly, cooperate and be actively involved in their education. After that, this research shows that getting children used to implementing the 3S queuing culture (smile, greet, greet) has a good impact because students become more orderly. The focus of this research is, what is the form of habituation to cultural implementation in class III students at MI asy-syifa, then how do you encourage students to remain consistent in implementing cultural implementation and what is the effect on student behavior after implementing cultural implementation in class III students? The purpose of this research is to determine the form of habituation to cultural implementation in students, and to find out how to encourage students to remain consistent in implementing cultural implementation at MI asy-syifa and to determine the influence on student behavior after implementing culture at school. This type of research uses a qualitative approach using data collection techniques in the form of observation, interviews and documentation. The implementation of school culture at Madrasah Ibtidaiyah Asy-Syifa has had a positive impact on the formation of student character. Learning, extracurricular and student conditioning activities involve a culture of queuing and the application of 3S (smile, greet, salute). The formation of student character requires time and consistency in the acculturation process, and the success of student character formation is closely related to the implementation of good school culture. Through the implementation of school culture, character values such as example, friendliness and discipline can be realized. In this context, teaching about queuing culture on an ongoing basis both in class and in extracurricular activities is considered important to shape student character.